Penanganan Perlindungan Hak Pengungsi Anak dari Timur Tengah dalam Rumah Detensi Imigrasi Jakarta, Semarang, Surabaya - ita kumala sari (Journal of International Relations Diponegoro, 2023)
The purpose of this research is to know and understand Indonesian government effort or actions on protecting Human Rights for child refugee that live in Indonesia’s Immigrant Detention House. This research used the concept of Human security and qualitative method for the research analysis. The results of this research explain that Rudenim Jakarta, Semarang and Surabaya in the fulfillment of human rights of the displaced children are in accordance with the Regulations the Director General of Immigration Number F-1002.PR.02.10 of 2006 and the United Nations Development Programme 1994 on a structured and overall handling and procedures for the placement of a stranger. I recommend that Immigrant Detention House in Jakarta, Semarang and Surabaya to coordinate more efficiently with related agency or institution, and increase their Human resources so they will be able to perform maximally in handling Child Refugee’s rigths. Indonesian Government should also make a policy that could clearly state and explain the status of asylum seeker in Indonesia to fulfill their rights.